Carotenoids, chlorophylls and pectins during ripening of guava (Psidium guajava L.) from Santander, Colombia (2018)
We evaluated the contents of carotenoids, chlorophyll and pectin in guava fruit, Psidium guajava L., in three locations (Barbosa, Puente Nacional, and Velez) in Santander Department, Colombia in four varieties (Regional Blanca, Raquira Blanca, Guavata Victoria, Regional Roja) for four stages of maturity (green, physiological maturity, semi- ripe, ripe). The total carotenoids and chlorophyll were determined with spectrophotometry, differentiating the endocarp, exocarp and pectins using the gravimetric method. The results were statistically significant (P≤0.05), obtaining the highest contents of carotenoids in the variety Regional Roja (166.3 mg/100 g, semi-rate state in Barbosa), the highest chlorophyll in Guavata Victoria (39.87 mg/100 g, green state in Vélez) and the highest pectins in Regional Blanca (1.79%p/p, physiological maturity state, in Puente Nacional). The white fleshed varieties (Regional Blanca, Raquira Blanca and Guavata Victoria) had higher contents of carotenoids in the exocarp (11.19 mg/100 g), unlike the Regional Roja variety, which had a high content in the endocarp (13.06 mg/100 g). The principal component analysis (PCA) and cluster analysis showed a direct relationship between the carotenoids, chlorophyll and pectin in white-fleshed varieties, in contrast to in the inverse relationship found in the Regional Roja variety.